Air Pollution Exposure and Risk of Spontaneous Pneumothorax in Children: A Longitudinal, Nationwide Study - Jing-Cheng Wang; Cheng-Li Lin; Chieh-Ho Chen; Chien-Heng Lin (MDPI AG, 2022)
Spontaneous pneumothorax (SP) involves the spontaneous appearance of air in the pleural space. Atmospheric pressure, temperature change, and seasonal factors may precipitate SP, but its association with air pollution remains unclear. Therefore, we conducted this nationwide, retrospective population-based study to evaluate the risk of SP in Taiwanese children exposed to air pollution. We collected data on SP incidence from the Longitudinal Health Insurance Database; the Taiwan Air Quality-Monitoring Database provided daily concentrations of nitric oxide (NO), nitrogen dioxide (NO2), and hydrocarbons in 2000-2012. SP risk was evaluated for four quartiles (Q1, Q2, Q3, Q4). The NO adjusted hazard ratios (aHRs) for Q2, Q3, and Q4 compared to Q1 were 1.11 (95% confidence interval (CI): 0.77-1.61), 1.24 (95% CI: 0.88-1.76), and 1.66 (95% CI: 1.17-2.34), respectively. The NO2 aHRs for Q2, Q3, and Q4 were 1.12 (95% CI: 0.77-1.64), 1.31 (95% CI: 0.0.90-1.90), and 1.51 (95% CI: 1.04-2.19), respectively. Hydrocarbons aHRs for Q2, Q3, and Q4 were 0.87 (95% CI: 0.64-1.18), 1.16 (95% CI: 0.90-1.49), and 1.40 (95% CI: 1.06-1.85), respectively. Increased exposure to NO, NO2, and hydrocarbons is associated with increased SP risk in Taiwanese children.